Effects of two exercise protocols on postural balance of elderly women: a randomized controlled trial - Mesquita, Laiana Sepúlveda de Andrade (BMC Geriatr, 2015)
BACKGROUND: The aging process reduces both sensory capabilities and the capabilities of the motor systems responsible for postural control, resulting in a high number of falls among the elderly. Some therapeutic interventions can directly interrupt this process, including physical exercise. This study compares and examines the effects of two exercise protocols on the balance of elderly women. METHODS: Elderly women who participated in a local church project (n = 63) were randomly divided into three groups: the proprioceptive neuromuscular facilitation group (PNFG), Pilates group (PG), and control group (CG). Of the 63 women, 58 completed the program. A training program involving 50-min sessions was performed in the PNFG and PG three times a week for 4 weeks. The elderly women in the CG received no intervention and continued with their daily activities. Stabilometric parameters, the Berg Balance Scale score, functional reach test, and timed up and go test (TUG test) were assessed before and 1 month after participation. RESULTS: In the comparison among groups, the women in the PNFG showed a significant reduction in most of the stabilometric parameters evaluated and better Berg Balance Scale score, functional reach test result, and TUG test result than did women in the CG (p < 0.05). Women in the PG showed significantly better performance on the functional reach test and TUG test than did women in the CG (p < 0.05). CONCLUSIONS: Women in the PNFG showed significantly better static and dynamic balance than did women in the CG. Women in the PG also showed better dynamic balance than did women in the CG. However, no significant differences were observed in any of the balance variables assessed between the PNFG and PG. TRIAL REGISTRATION: clinicaltrials.gov, number NCT02278731